ANALYSIS OF LEADING STAPLE FOOD CROP COMMODITIES IN NGADA REGENCY - Kila, Kornelia; Nurwiana, Ida; Darlen, Maria Fransiska; Adar, Damianus (Undana Press, 2025)
Ngada Regency is an area that has land conditions and climate potential that vary in characteristics. The diversity of physical characteristics of land will determine the types of commodities that can be cultivated and will influence the level of productivity. Therefore, determining superior commodities is very necessary for decisions on future commodity development. The objectives of this research are: 1). Knowing superior commodities for staple food crops using the Dynamic Location Quetient (DLQ) analysis approach based on harvest and production area data 2). Identify staple food crop commodities that have the potential to be developed and have competitive advantages using the Shift Share Analysis (SSA) approach. This research uses a quantitative approach using secondary data from the Central Statistics Agency (BPS) of Ngada Regency for the 2018-2022 period. The research results show that the leading commodities in Ngada Regency are Sweet Potatoes, Cassava, Rice, Corn and Peanuts, where these commodities have a progressive growth rate and are competitive. The sweet potato commodity is a commodity that has a progressive growth rate and has good competitiveness in almost all sub-districts.